PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA GHAISAN BOUTIQUE SUKABUMI - Bintang, Femilia; Rianto, Toha (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
This study aims to determine the influence of product quality and brand image on purchasing decisions in the online store Ghaisan Boutique Sukabumi. The research method used in this study is a quantitative descriptive method. The descriptive method is a research method that seeks to describe and interpret an existing condition or relationship, a developing opinion, an ongoing process, an effect or effect that occurs, or an ongoing trend. The results of the study show that the influence of Product Quality has a significant impact on the Purchase Decision, where from the results of the partial test the value of the product quality calculation is greater when compared to the table, namely the tcount (5.881) > the table (2.0141) and the significance is 0.000 < 0.05, (below 0.05). Thus the first hypothesis (H1) is accepted and H0 is rejected. Brand Image does not have a significant effect on the Purchase Decision, where based on the t-test or partially, the value of the brand image on the purchase decision is calculated (1.528) < ttable (2.0141) and or the significance of t (0.133) > 0.05, indicating that the tcalculated value is below the ttable which means that H0 is accepted and H1 is rejected. The influence of Product Quality and Brand Image has a significant impact on Purchase Decisions. This is shown by the value of Fcal (17.349) > Ftabel (3.19) and the significance value is 0.000 which is below 0.05, meaning that H0 = rejected and H1 = accepted. This can be interpreted if together the quality of the product and the brand image will significantly affect consumer purchasing decisions.